Analysis of the brand value of Marathon sports in the city of Machala - Matamoros Ramos, Fabricio; Rivera Valarezo, Adriano; Aguilar Gálvez, William (mktDESCUBRE; Vol 1 No 21 (2023): Twenty-first Edition (January - June), 2023)
The following scientific article aims to analyze the variables that significantly influence the brand value of the company Marathon Sports in the city of Machala and its relationship with the purchase intention; A correlational study was conducted with a quantitative methodology based on PLS-SEM (Partial Least Squares Structural Equation Modeling), using a structural design based on David Aaker's model, a Likert-type questionnaire was applied where 223 people were surveyed, The data were interpreted with the statistical software Smart PLS and the results showed that the variables brand awareness (CM), perceived quality (CP) and brand loyalty (LM) have a significant influence on brand value (MV), and the latter influences purchase intention (PI). In this way, a real market situation focused on sports products in this selected segment was diagnosed.